The Importance of the Mean Platelet Aggregation Degree in Long‐term Dual Antiplatelet Therapy Following Drug‐Eluting Stent Implantation. Issue 3 (June 2016) - Li, Quan; Ren, Xuejun; Yu, Xianpeng; He, Jiqiang; Gao, Yuechun; Zhang, Xiaoling; Wu, Changyan; Luo, Yawei; Zhang, Yuchen; Chen, Fang
Summary: Introduction: The dual antiplatelet therapy (DAPT) and the response of clopidogrel were two pivotal issues in drug‐eluting stent (DES) era. Aims: To analyze the combined impacts of DAPT and the response to clopidogrel to evaluate their long‐term effect on patients undergoing DES implantation. Methods: Platelet aggregation was serially measured by light transmission aggregometry in all eligible patients during the course of treatment with DAPT, and the mean platelet aggregation degree of each participant was calculated. Based on the duration of DAPT and the mean platelet aggregation degree, all the enrolled patients were then divided into four groups. The primary endpoint was a composite of major adverse cardiovascular events. Results: We analyzed 1245 suitable patients in this study. They were divided into four groups: Group A (12‐month DAPT & low platelet aggregation degree) with 233 subjects, Group B (12‐month DAPT & high platelet aggregation degree) with 260 subjects, Group C (>12‐month DAPT & low platelet aggregation degree) with 374 subjects, and Group D (>12‐month DAPT & high platelet aggregation degree) with 378 subjects. Group C was associated with a decreased incidence of primary endpoints [HR 0.512, 95%CI (0.27–0.97); P = 0.040]. The Cox proportional hazard model was further analyzed with Groups A and B combined as the reference category [HR for Group C vs. Group A, 0.84, 95%CI (0.33–2.15); P = 0.719; HR for Group C vs. Group B, 0.45, 95%CI (0.21–0.98); P = 0.043]. Their respective multivariate Cox proportional hazard regressions confirmed these trends. Conclusions: The mean platelet aggregation degree is of importance in long‐term use of DAPT; extension of DAPT beyond 1 year should be implemented cautiously in patients implanted with DESs.